George and the big bang - Hawking, Lucy (Simon & Schuster Books for Young Readers, 2012)
George tries to escape a host of problems by going to Switzerland to help his friend Annie's father, Eric, run an experiment exploring the origins of the universe, but faces saboteurs and a mysterious message from George's old nemesis, Reeper, there. Includes scientific essays exploring the latest theories on the origin of the universe.